Using geneid to Identify Genes. Issue 1 (17th October 2018) - Alioto, Tyler; Blanco, Enrique; Parra, Genís; Guigó, Roderic
Abstract: This unit describes the usage of geneid, an efficient gene‐finding program that allows for the analysis of large genomic sequences, including whole mammalian chromosomes. These sequences can be partially annotated, and geneid can be used to refine this initial annotation. Training geneid is relatively easy, and parameter configurations exist for a number of eukaryotic species. geneid produces output in a variety of standard formats. The results, thus, can be processed by a variety of software tools, including visualization programs. geneid software is in the public domain, and is undergoing constant development. It is easy to install and use. Exhaustive benchmark evaluations show that geneid compares favorably with other existing gene‐finding tools. © 2018 by John Wiley & Sons, Inc.